Determinación del costo del servicio de algunos servicios bajo la metodología ABC para el centro médico veterinario Scooby Doo de la ciudad de Palmira- Valle del Cauca (2024)
The main objective of the work is to analyze and accurately calculate the costs associated with certain surgeries in the aforementioned veterinary medical center. To achieve this, the Activity Based Costing (ABC) methodology is used, which provides a detailed and comprehensive approach to allocating costs.